Henry Macdonald Kyle (1872–1951): a Scottish pioneer of international fisheries research. Issue 1 (April 2017) - Moore, P. G.; Kyle, R.
Abstract : Little is known of Henry (Harry) Macdonald Kyle and his scientific contributions even within some fisheries research circles. A graduate of St Andrews University and a protégé of William Carmichael McIntosh, in 1903 – the year after its inception – he was appointed as Biological Secretary to the International Council for the Exploration of the Sea (ICES), based in Copenhagen. An expert on flatfishes (notably Plaice), he worked with Walter Garstang at Plymouth but latterly, in extensive collaboration with Ernst Ehrenbaum at Hamburg, he produced definitive works analysing the fishery statistics of European fisheries addressing, in particular, the issue of overfishing. In the late 1920s and early 1930s, however, he became alienated from his wife and children, even in correspondence referring to himself as an outcast (though later he was reconciled to at least one of his sisters). Little is known of the final decades of his life, apart from the fact that he died in his native Scotland. An accomplished linguist, he translated the works of many of his Danish and German colleagues into English. He published his magnum opus on the fisheries of Great Britain and Ireland in German. His earlier book, The biology of fishes, while published in English, was dedicated to his German friend Ehrenbaum. For whatever reasons he found life in Germany more conducive to his work and, in some recent literature, he has even been assumed to have been German.